Schistosoma japonicum Infection in Treg-Specific USP21 Knockout Mice - Youxiang Zhang; De-Hui Xiong; Yangyang Li; Guina Xu; Baoxin Zhang; Yang Liu; Shan Zhang; Qing Huang; Simin Chen; Fansheng Zeng; Jingyi Guo; Bin Li; et al. (Journal of Immunology Research)
The E3 deubiquitinating enzyme ubiquitin-specific proteolytic enzyme 21 (USP21) plays vital roles in physiological activities and is required for Treg-cell-mediated immune tolerance. Using a murine model infected with Schistosoma japonicum, we observed that there were more cercariae developed into adults and more eggs deposited in the livers of the USP21fl/flFOXP3Cre (KO) mice. However, immunohistochemistry showed that the degree of egg granuloma formation and liver fibrosis was reduced. In USP21fl/flFOXP3Cre mice, levels of IFN-gamma, IL-4, anti-soluble egg antigen (SEA) IgG and anti-soluble worm antigen preparation (SWAP) IgG increased in blood, as determined using ELISAs and multiplex fluorescent microsphere immunoassays, while the levels of IL-10, lL-17A, IL-23, IL-9, and anti-SEA IgM decreased. In addition, the levels of the USP21 protein and mRNA in the liver and spleen of KO mice decreased. We further observed increased Th1 responses amplified by Tregs (regulatory T cells) and compromised Th17 responses, which alleviated the liver immunopathology. We speculated that these changes were related to polarization of Th1-like Tregs. Our results revealed the roles of USP21 in Treg-cell-mediated regulation of immune interactions between Schistosoma and its host. USP21 may have potential for regulating hepatic fibrosis in patients with schistosomiasis.